ANALISIS PERSEPSI MAHASISWA AKUNTANSI TERHADAP KODE ETIK AKUNTAN - Risa, Nurma (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2010)
This study purposes to examine wether there is different perception of the ethic code ofthe Indonesian accountants associate between accounting students on individual factors (year ofstudy, program, GPA (Geade Point Average), gender, and job experience), and to find out theadequacy of ethic in accounting curriculum. The populations of this research are accountingstudent in Universitas Islam ?45 Bekasi (UNISMA Bekasi) who still in the first and last year. Theanalysis of this research using independent sample t-test dan Mann whithney u-test as aconfirmation.The result of hypothesis test shows there is significantly ethical perception differences between first year student and last year student. And there is no signifantly ethical perception differences between diploma student and bachelor student, between male and female student, between student with GPA more than three and less than three, and between working student and not working student.The result of survey of adequacy of ethic in accounting curriculum show that the recent accounting curriculum is not adequate to give ethical lesson for the student when they are working.